The History of Social Movements in Global Perspective
XVII, 720 p.
Keywords: Social movements have shaped and are shaping modern societies around the globe; this is evident when we look at examples such as the Arab Spring, Spain’s Indignados and the wider Occupy movement. In this volume, experts analyse the ‘classic’ and new social movements from a uniquely global perspective and offer insights in current theoretical discussions on social mobilisation. Chapters are devoted both to the study of continental developments of social movements going back to the nineteenth century and ranging to the present day, and to an emphasis on the transnational dimension of these movements. Interdisciplinary and truly international, this book is an essential text on social movements for historians, political scientists, sociologists, philosophers and social scientists.